Schwellenzeiten - Atwood, David (Ergon Verlag, 2019)
Describing the boundaries of what society conceives as 'religion' means establishing a social order with its respective areas of politics, law, or science. These areas are sometimes opposed to what we conceal as 'religion'. In this book, the social boundaries of religion are explored with a specific focus on threshold narratives in the contemporary history of religion. Threshold narratives, as mythopoetic forms of social self-description, are used to describe a new origin that not only includes a diagnosis, but also proposes a therapy to treat the diagnosed crisis. The positioning and limitation of religion in these threshold narratives is the condition that makes 'religion' governable. The analysis follows different metaphors of European religious history: the 'end', the 'axis' and the 'hour zero'.